2016
DOI: 10.1080/19396368.2016.1212949
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal polymorphic variants increase aneuploidies in male gametes and embryos

Abstract: FISH: fluorescent in situ hybridization; CGH: comparative genomic hybridization; ESHRE: European Society of Human Reproduction and Embryology; ASRM: American Society for Reproductive Medicine; RPL: recurrent pregnancy loss; WHO: World Health Organization; ISCN: International System for Human Cytogenetic Nomenclature guidelines; WGA: whole genome amplification; SPSS: Statistical Package for Social Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
2
26
1
Order By: Relevance
“…Similar study by Morales et al found that the frequency of infertile men with increased rates of sperm aneuploidy was higher among polymorphism carriers. (37.7 vs 16.3%), proved a relationship between polymorphisms and aneuploidy in spermatozoa and embryos [33].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar study by Morales et al found that the frequency of infertile men with increased rates of sperm aneuploidy was higher among polymorphism carriers. (37.7 vs 16.3%), proved a relationship between polymorphisms and aneuploidy in spermatozoa and embryos [33].…”
Section: Discussionmentioning
confidence: 87%
“…Some previous studies reported that chromosomal polymorphism had a high incidence rate in infertile couples [15,24,25] and couples with recurrent miscarriage [16,17,34,35]; However, there was no apparent adverse effect in IVF treatment in some studies [12,13]. The possible mechanism is couples with chromosomal polymorphic variants may be more likely to produce sperm [32,33] and embryos [33] with abnormal chromosomal components; these abnormal chromosomic embryos can be seen as multinucleation in embryo culture [6,8]; furthermore, these embryos may lead to infertility and/or recurrent miscarriage in natural conception. However, during IVF, because more embryos are prepared after ovarian stimulation, we can select suitable embryos (e.g., without multinucleation) to transfer even in couples with chromosomal polymorphic variants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some heterochromatic regions can cause susceptibility to unequal recombination of homologues during cell division and induce chromosomal aberrations such as inversions, deletions, or extensions [17]. And large heterochromatic blocks of different polymorphic types can interfere with the process of chromosomal synapsis and spindle fiber attachment, leading to meiotic errors or arrest [18] and causing gamete and embryo aneuploidy [19]. Yakin K et al analyzed sperm aneuploidy using fluorescence in situ hybridization (FISH) in 54 infertile men with normal peripheral karyotypes and 8 men with chromosomal polymorphisms and found that there is a prominently high incidence of aneuploidy in sperm of polymorphism carriers, and in this study, the dominant polymorphic types were 9qh+ and 16h+ [15].…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51] A recent study showed an increase in the frequency of polymorphic variants among infertile patients (19.4% in the study group vs. 13.4% in the control group; p< 0.01). 51 Of the 17 studies included in this review, only six have assessed miscarriage material ( Table 2). Two of them referred not having reached the results and the cell culture failure in the cytogenetic analysis (CA).…”
Section: Discussionmentioning
confidence: 94%